A Study on Dorsal Pedicled Tongue Flap Closure of Palatal Fistulae and Oronasal Communications - Jeyaraj, Priya Esther (Ann Maxillofac Surg, 2017)
INTRODUCTION: Residual defects of the palatal region following ablative resection of tumors and Gunshot wounds (GSWs) of the maxillofacial region can be quite painstaking, daunting and challenging to reconstruct, due to the extent and composite nature of the tissue loss. A shortage of available donor areas and local flap options in the intraoral region, add to the difficulty. Further compounding the situation, are factors such as excessive fibrosis and scarring of the palatal tissues as a result of multiple previous surgeries in the region. OBJECTIVE: To evaluate the effectiveness of the Dorsal Pedicled Tongue Flap in the reconstruction of complex palatal defects resulting from maxillofacial GSWs and ablative tumor resections. To also device techniques to reduce the incidence of postoperative tongue flap detachment, thus improving its efficiency and reliability. RESULTS: The palatal fistulas in all the patients were closed successfully, with no post-operative complications such as bleeding, hematoma formation, congestion, infection, partial or total flap necrosis or flap detachment. The tongue flap at the recipient site remained healthy with no recurrence of the fistula in any of the patients in the two years follow up period. There was a complete resolution of the problem of nasal regurgitation of orally ingested fluids and food particles. There was observed no deformity or articulation defect resulting from the flap harvested from the tongue dorsum, in any of the patients. CONCLUSION: In GSWs and tumor ablative surgery, where composite tissue defects are involved, the tongue provides a reliable and efficient means of restoring lost tissue bulk as well as ensuring a permanent closure and sealing off of the oronasal fistulas. Its reliability can be further increased by avoiding a common complication, namely, flap detachment in the postoperative period brought on by movements of the tongue, by immobilizing the tongue by tethering it to the maxillary teeth and also, maintaining the patient on Nasogastric feeding for the three weeks postoperative period, until the patient is taken up for surgical separation the pedicle. This helps to ensure a successful and predictable take of the flap at the donor site.